Continuous Online Assessment at a South African Open Distance and e-Learning Institution - Fynn, Angelo; Mashile, Elias Oupa (Frontiers in Education, 2022)
Online assessment and continuous assessment are gaining growing attention from the assessment community. In particular the merger of these two forms of assessment is becoming popular for implementing assessment at scale. In this paper we investigate student experiences of the implementation of online continuous assessment at an Open, Distance and e-Learning institution. This study describes the impact of this rapid shift to continuous online assessment, sparked by the COVID pandemic, from the perspectives of students, many of whom were confronted with online assessments for the first time. The South African higher education landscape is marked with inequalities in schooling, internet access, device access and financial resources as it is one of the most unequal countries in the world. An institution wide survey was administered electronically to all students who had taken at least one online continuous assessment module in 2020. Students completed open ended questions about their experiences of undertaking online continuous assessment during the 2020 academic year. The findings of this study found that many students were not adequately prepared for the substantial increase in workload that continuous online assessment entailed; that assessment structures disadvantaged certain groups of students, especially those who worked or managed households; that students’ access to devices and internet were grossly unequal which had a negative effect on their experience of the transition to continuous, online assessment.